ENHANCING THE TEACHING OF FUNDAMENTALS OF INFORMATION TECHNOLOGY (AIS160): A PEDAGOGICAL INVESTIGATION - Ahmad Zoolhelmi Alias; Nik Nurul Aswani Nik Kamaruddin; Salina Mad; Mohd Zulfikri Abd Rashid; Mohd Soffi Puteh (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the impact of interactive and experiential pedagogical strategies on the teaching and learning of the Fundamentals of Information Technology (AIS160) course at Universiti Teknologi MARA (UiTM) Perak Branch, Tapah Campus. Using a mixed-methods design, data were collected from 81 diploma-level students and four instructors through structured questionnaires and semi-structured interviews. The study is grounded in Constructivism, Kolb’s Experiential Learning Theory, and the Technological Pedagogical Content Knowledge (TPACK) framework. Quantitative findings reveal that most students reported increased motivation, satisfaction, and understanding of IT concepts following the implementation of hands-on, real-world learning activities. Qualitative data highlight key themes including student preference for gamified assessments, multimedia resources, and collaborative tasks. Instructors noted improved engagement but identified challenges such as limited infrastructure and digital inequity. The results support the integration of experiential and interactive strategies in foundational IT education and underline the need for institutional support and curriculum alignment. Recommendations include enhancing technological infrastructure, promoting peer collaboration, and aligning assessment practices with experiential learning objectives. The study contributes to ongoing discourse on pedagogical innovation in higher education and offers practical insights for improving digital learning environments.